(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2025)
Giambattista Vico’s (1668-1744) philosophy proposes a model of poetic creation closely related to pictorial work. If in the first New Science (1725) – dedicated to the broader issue of the «common nature of nations» – the poetic language of primitive peoples is defined as a «painted speech», in the contemporary letter to Gherardo degli Angioli the association of painting and poetry concerns the specific domain of art. Relying on the analysis of this letter, written as a commentary on some sonnets sent to him by a young student, the aim of the paper is to demonstrate how the Neapolitan philosopher challenges the mimetic paradigm of art, maintaining at the same time the principle of similarity between the two arts. Therefore, the inventive model of artistic creation offered by Vico appears alternative to what will be proposed by Lessing in his famous Laocoon (1766), where criticism of the concept of art as mimesis will result from the divorce between poetry and painting. On the contrary, for Vico, both poetry and painting do not produce copies of reality but sensible ideas. In this way, it is precisely painting that reveals the essence of artistic praxis – constituting also a model for literary creation – insofar as it constructs its ideas in an immediately sensible manner, without passing through the abstraction inherent in verbal language.